Human dendritic cell interactions with the zoonotic parasite Cryptosporidium parvum result in activation and maturation - Ross, Ralf; Hasheminasab, Seyed Sajjad; Conejeros, Iván; Gärtner, Ulrich; Kamena, Faustin; Krueger, Andreas; Taubert, Anja; Hermosilla, Carlos (Frontiers in Immunology, 2024)
Cryptosporidiosis is caused in humans by infection with the zoonotic apicomplexan parasite Cryptosporidium parvum. In 2006 it was included by the World Health Organization (WHO) in the group of the most neglected poverty-related diseases. It is characterized by enteritis accompanied by profuse catharralic diarrhea with high morbidity and mortality, especially in children of developing countries under the age of 5 years and in HIV-patients. The vulnerability of HIV-patients indicates that a robust adaptive immune response is required to successfully fight this parasite. Little is known, however, about the adaptive immune response against C. parvum. To get an insight into the early events of the adaptive immune response we generated primary human DC from monocytes of healthy blood donors and exposed them to C. parvum oocysts and sporozoites in vitro. DC are equipped with numerous receptors that detect microbial molecules and alarm signals. If stimulation is strong enough an essential maturation process turns DC into unique activators of naïve T cells, a pre-requisite of any adaptive immune response. Parasite exposure highly induced the production of the pro-inflammatory cytokines/chemokines IL-6 and IL-8 in DC. Moreover, antigen-presenting molecules (HLA-DR, CD1a), maturation markers and costimulatory molecules required for T cell stimulation (CD83, CD40, CD86) and adhesion molecules (CD11b, CD58) were all upregulated. In addition, parasite-exposed human DC showed enhanced cell adherence, increased mobility and a boosted, but time-limited phagocytosis of C. parvum oocysts and sporozoites, representing other prerequisites for antigen presentation. Unlike several other microbial stimuli, C. parvum exposure rather led to increased oxidative consumption rates (OCR) than extracellular acidification rates (ECAR) in DC, indicating that different metabolic pathways were used to provide energy for DC activation. Taken together, C. parvum-exposed human DC showed all hallmarks of successful maturation enabling them to mount an effective adaptive immune response.